2014
DOI: 10.1186/1471-2261-14-100
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel discontinuation within the first year after coronary drug-eluting stent implantation: an observational study

Abstract: BackgroundThe impact of adherence to the recommended duration of dual antiplatelet therapy after first generation drug-eluting stent implantation is difficult to assess in real-world settings and limited data are available.MethodsWe followed 4,154 patients treated with coronary drug-eluting stents in Western Denmark for 1 year and obtained data on redeemed clopidogrel prescriptions and major adverse cardiovascular events (MACE, i.e., cardiac death, myocardial infarction, or stent thrombosis) from medical datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Patient antithrombotic medication adherence following placement of a drug-eluting stent (DES) is a challenge as 5.4% of patients never fill a prescription and on average, patients have their medication only 81% of the time over a year (1). Non-adherence to antithrombotic medication leads to a nine times greater risk of death within the first year of the stent placement (25).…”
Section: Introductionmentioning
confidence: 99%
“…Patient antithrombotic medication adherence following placement of a drug-eluting stent (DES) is a challenge as 5.4% of patients never fill a prescription and on average, patients have their medication only 81% of the time over a year (1). Non-adherence to antithrombotic medication leads to a nine times greater risk of death within the first year of the stent placement (25).…”
Section: Introductionmentioning
confidence: 99%
“…The level of adherence was estimated based on patients' declarations only, which was a major limitation of the study. A different study reported the increase of MACE due to discontinuation of clopidogrel within the initial 3-month period, but not after 3 to 12 months [46].…”
Section: Adherence After Ami Treated By Pcimentioning
confidence: 99%
“…Recently, some studies have suggested increased risk of recurrent cardiovascular events after planned cessation of clopidogrel therapy. It has been postulated that it could be due to increased platelet reactivity compared with pre-treatment values (platelet rebound) [1,[5][6][7][8][9]. However, in many previous studies [3,4,10], platelet reactivity before introducing clopidogrel was not assessed, and therefore it is unclear whether platelet reactivity after withdrawal was any higher than pre-treatment levels [1].…”
Section: Introductionmentioning
confidence: 86%